2019
DOI: 10.1128/jcm.00213-19
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Visibility on Rectal Swabs Used To Detect Enteropathogens: a Prospective Cohort Study

Abstract: Data are lacking regarding the impact of visible pigment on rectal swab diagnostic accuracy. We describe the test characteristics of rectal swabs with and without pigment in children with gastroenteritis. Between December 2014 and September 2017, children (age, <18 years) with ≥3 episodes of vomiting and/or diarrhea in a 24-h period and symptoms for <7 days were enrolled through two pediatric emergency departments and from a province-wide nursing telephone advice line in Alberta, Canada. Specimens were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…44 However, recent interrogations of this relationship have concluded that testing rectal swabs that lack visible feces is worthwhile for the PCR detection of common enteric bacteria and viruses. 44,45 Our results further corroborate this conclusion in the context of a protozoan diagnostic, as we observed no difference in rectal swab sensitivity when controlling for visible feces. There was an indication that C q values were slightly lower in rectal swabs with visible stool, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 85%
“…44 However, recent interrogations of this relationship have concluded that testing rectal swabs that lack visible feces is worthwhile for the PCR detection of common enteric bacteria and viruses. 44,45 Our results further corroborate this conclusion in the context of a protozoan diagnostic, as we observed no difference in rectal swab sensitivity when controlling for visible feces. There was an indication that C q values were slightly lower in rectal swabs with visible stool, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 85%
“…All children with AGE, regardless of disease severity, who consented to participate submitted specimens for testing. Notably we included children with isolated vomiting and were able to routinely detect pathogens, through the use of rectal swabs [31]. Including children with isolated vomiting and those not seeking care enabled our cohort to provide a unique and comprehensive picture of pediatric norovirus AGE.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an important advance in specimen collection includes the use of rectal swabs to expedite specimen acquisition at the point of care. Rectal swab specimens have acceptable sensitivity compared with paired bulk stool specimens ( 13 to 15 ), including when tested using the BioFire FilmArray gastrointestinal panel ( 12 ), and superior overall yield, due to higher collection rates ( 15 ). Thus, we hypothesized that use of the BioFire FilmArray gastrointestinal panel with stool, or rectal swab specimens when the former was not immediately available, would lead to a more targeted monitoring and therapeutic approach to the management of children with acute bloody diarrhea.…”
Section: Introductionmentioning
confidence: 99%